2016
DOI: 10.1080/09205063.2016.1155879
|View full text |Cite
|
Sign up to set email alerts
|

Novel fiber-based pure chitosan scaffold for tendon augmentation: biomechanical and cell biological evaluation

Abstract: One possibility to improve the mechanical properties after tendon ruptures is augmentation with a scaffold. Based on wet spinning technology, chitosan fibres were processed to a novel pure high-grade multifilament yarn with reproducible quality. The fibres were braided to obtain a 3D tendon scaffold. The CS fibres and scaffolds were evaluated biomechanically and compared to human supraspinatus (SSP) tendons. For the cytobiological characterization, in vitro cell culture experiments with human mesenchymal stem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…The tensile strength (10.1±1.4 MPa in the nanofiber yarn direction, and 62.0±8.8 MPa in the multifilament yarn direction) and strain (45.3±8.2 % in the nanofiber yarn direction, and 40.9±4.0 % in the multifilament yarn direction) of the woven fabrics were comparable to the native human tendon [66, 67]. Nowotny et al reported a mean ultimate stress value of 3.9±0.7 MPa and mean ultimate strain value of 35.8±8.4 % for supraspinatus tendons [66]. Another study measured the tensile properties in different location of human supraspinatus tendons [67].…”
Section: Discussionmentioning
confidence: 99%
“…The tensile strength (10.1±1.4 MPa in the nanofiber yarn direction, and 62.0±8.8 MPa in the multifilament yarn direction) and strain (45.3±8.2 % in the nanofiber yarn direction, and 40.9±4.0 % in the multifilament yarn direction) of the woven fabrics were comparable to the native human tendon [66, 67]. Nowotny et al reported a mean ultimate stress value of 3.9±0.7 MPa and mean ultimate strain value of 35.8±8.4 % for supraspinatus tendons [66]. Another study measured the tensile properties in different location of human supraspinatus tendons [67].…”
Section: Discussionmentioning
confidence: 99%
“…These contructs consist of an acellular scaffold providing mechanical stability, and a seeded cell line providing regeneration and tissue function. Several scaffold materials have been used with some success so far, such as chitosan, silk fibroin, PLGA or decellularized cadaver tendons [1][2][3][4] . Compared to other cell lines such as skin fibroblast and adipose stem cells 5,6 , tenocytes seem highly suitable or scaffold seeding as the most original cell line 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, many applications could be achieved by preparation of fibers in other textile forms using knitting, weaving, or braiding since the textile mimics important mechanical characteristics of native tissue. For example, the bundle of parallel fibers could serve as a template in nerve regeneration, braided 3 D scaffold in tendon regeneration or meshed scaffold in cartilage tissue repair, where HA can be naturally found. Nanofibers from various materials are often used for the same applications as scaffolds mimicking more accurately the native tissue .…”
Section: Resultsmentioning
confidence: 99%